Exploration of the Application of the Project Based Learning Approach Based on Banana Tree Media in Stimulating Creativity in Early Childhood - Dessy Syofiyanti; Hasnida; Muh. Misbah (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Creativity is a fundamental competency in early childhood education because it supports children's ability to generate ideas, solve problems, and express themselves through meaningful learning experiences. However, learning activities in many early childhood classrooms remain predominantly teacher-centered, limiting opportunities for children to explore, experiment, and develop original ideas. This study aimed to explore the implementation of Project-Based Learning (PjBL) utilizing banana tree media and its role in stimulating creativity among children aged 5–6 years. A qualitative descriptive approach was employed involving twelve children and one classroom teacher at TK Ceria Eduloka, Indonesia. Data were collected through classroom observations, semi-structured interviews, and documentation, and were analyzed using the interactive model of data reduction, data display, and conclusion drawing. The findings revealed that project-based activities using banana leaves, stalks, and trunks encouraged children to actively participate in exploration, decision-making, material manipulation, and creative product development. Children demonstrated creativity through fluency in generating ideas, flexibility in using materials, originality in creating products, and elaboration in refining their work. The findings further indicate that banana tree media provide contextual, multisensory, and environmentally relevant learning experiences that enhance children's engagement and creative expression. This study contributes to the growing literature on project-based and nature-based learning by highlighting the educational potential of locally available natural resources in fostering creativity. Practically, the findings offer an accessible and cost-effective strategy for implementing meaningful learning experiences in early childhood education.